Subcutaneous Nephrovesical Bypass in Kidney Transplanted Patients - Yazdani, M. (Avicenna Organ Transplantation Institute, 2010)
Background: Renal transplant ureteral stricture or obstruction is a rare but devastating complication after renal transplantation. Objective: To determine the efficacy and complications of subcutaneous prosthetic ureters as a salvage procedure in transplanted kidneys with recurrent ureteral obstruction. Methods: 5 subcutaneous prosthetic ureters were inserted in 5 kidney recipients who had recurrent ureteral stenosis and failed endoscopic and open reconstructive surgeries. The prosthetic ureter consisted of an internal silicone tube covered by a coiled PTFE tube. The proximal end of the tube was introduced in the transplanted kidney percutaneously, the tube was passed through a subcutaneous tunnel, and the distal end was inserted in the bladder through a small suprapubic incision. Results: The mean follow-up of patients was 11.3 months. One of the patients re-operated two days after the procedure because of urinary leakage from the distal end of the prosthetic ureter. No infection or tube encrustation was encountered. Conclusion: Subcutaneous prosthetic ureter is a safe alternative for permanent percutaneous nephrostomy in transplanted kidneys with obstructed ureter and failed endoscopic and open procedures.